Reason for immigration and immigrants' health - Giuntella, O; Kone, Z; Ruiz, I; Vargas-Silva, C (Elsevier, 2018)
Objectives The existing literature on the health trajectories of the UK immigrants has mainly focussed on the relationship between ethnicity and health. There is little information on the role of immigration status and no previous information on the role of reason for immigration to the country. This study fills this gap in the literature by analysing the heterogeneity of immigrant-native differences in health by reason for immigration. Study design Analysis of cross-sectional quarterly data from the UK Labour Force Survey covering the period of 2010 (quarter 1) to 2017 (quarter 2). The sample includes 345,086 observations. The dependent variables of interest include suffering from a long-lasting condition, the link between long-lasting conditions and labour market performance and the prevalence of 12 specific health conditions. Methods Data were analysed using linear probability models to adjust for differences in age, education, gender, ethnicity, local authority of residence and year of survey. The analysis also explores the role of length of stay in the UK and the percentage of current lifetime spent in the UK (duration in the UK/age). Results Results indicate that, in general, immigrants are less likely than natives to report suffering from a long-lasting (1 year or more) health problem. This pattern generally remains the same when we consider the specificity of the long-lasting health problem. However, there are key differences across the immigrant groups by reason for immigration. Those who migrated for employment, family and study reasons report better health outcomes than natives, while those who migrated to seek asylum report worse health outcomes than natives. There is convergence to natives' health outcomes over time for those who migrated for non-asylum reasons, but not for those who migrated to seek asylum. Conclusions The findings show that the prevalence of health problems differs not only between natives and immigrants but also across groups of immigrants who moved to the UK for different reasons.